Expression and localization of acrosin inhibitor in boar reproductive tract - Davidová, Nina; Jonáková, Vera; Manásková-Postlerová, Pavla (Cell and tissue research, 2009)
Proteinases and proteinase inhibitors play key roles in almost all physiological processes. Proteinase inhibitors are present in all tissues and body fluids. They interfere with the activity of proteinases and thus maintain homeostasis. The main role of proteinase inhibitors in the reproductive tract is the inactivation of prematurely released hydrolytic enzymes from damaged spermatozoa and the protection of reproductive tracts and spermatozoa against proteolytic degradation. In the boar reproductive system, acrosin inhibitors are found in seminal plasma and on spermatozoa. The amino acid sequence of seminal plasma and sperm-associated acrosin inhibitors is 90% identical, and their biochemical properties have been completely resolved. However, their origin and localization have not been fully elucidated. Using rabbit polyclonal antibody, we have studied the expression and localization of the seminal plasma acrosin inhibitor in the boar reproductive tract. The antibody recognizes a 12-kDa band in extracts from the cauda epididymidis, seminal vesicles, prostate, and Cowper's glands, and immunofluorescence has revealed the acrosin inhibitor in the epithelium and lumen of these organs. Gene expression of the acrosin inhibitor has been studied by reverse transcription together with the polymerase chain reaction. Acrosin inhibitor mRNA transcript is detectable in the epididymis, seminal vesicles, prostate, and Cowper's glands. The antibody has localized the acrosin inhibitor on the surface of epididymal and ejaculated spermatozoa in the acrosomal region. In extracts from epididymal and ejaculated spermatozoa, the specific antibody recognizes acrosin inhibitor at 8 kDa and 12 kDa. The presence of acrosin inhibitor on the sperm surface as a protective molecule for receptors mediating the sperm-zona pellucida binding suggests that it is crucial for the reproductive process.
Keywords: Trypsin Inhibitor, Kazal Pancreatic; fluorescenční protilátková technika; sperma; prostata; Acrosome; semenné váčky; Reproduction; epitel; rozmnožování; inhibitory proteas; Seminal Vesicles; sekreční proteiny semenných váčků; bulbouretrální žlázy; Bulbourethral Glands; Zona Pellucida; Seminal Vesicle Secretory Proteins; zvířata; akrozom; Swine; Epididymis; Male; Prostate; Epithelium; inhibitor trypsinu Kazal pankreatický; epididymis; Semen; zona pellucida; Fluorescent Antibody Technique; Animals; mužské pohlaví; Protease Inhibitors; prasata